Natural Research in the Fergana Valley of the XX Century - Hamidov Abdusamad Abdumalikovich (Central Asian Journal of Theoretical and Applied Science, 2022)
The article describes the study of the components of nature in the Fergana Valley in the second half of the twentieth century, based on its stage of development in space and time, in the fourth quarter of the twentieth century, the geoecological significance of the study in the Fergana Valley. The dynamics and scientific results of complex natural geographical researches carried out during the 2000s are described.